Pengaruh Pelaksanaan Ibadah Puasa terhadap Pendidikan Karakter Islam (Self Control) Mahasiswa Muslim di Universitas Negeri Medan - Fazril Anshari; Hapni Laila Siregar; Putri Nur Aini; Salsabila Zahra; Silvana Oyasi Ayu; Siti Zahra Sabila (IAIN Batusangkar, 2024)
Islamic character education is basically a general character education which contains various aspects of Islam to form Islamic characters that are based on Islamic teachings. One of character education is self-control. Self-control is an individual's ability to control behavior and impulses that can harm themselves or others. In Ramadan, as a month full of blessings for Muslims, fasting is expected to strengthen students' self-control abilities in their daily lives. This research aims to determine the impact of fasting on Muslim studentsÔÇÖ self-control at Medan State University. This research is motivated by an understanding of the importance of religious practices in students' lives, especially for psychological well-being and personal development. This research used a quantitative approach. Data were collected by distributing a questionnaire to Muslim students at Medan State University who observed fasting in Ramadan. Data analysis was carried out using descriptive statistical techniques to identify the relationship between fasting and students' level of self-control. The findings describe that there is a significant influence of fasting on studentsÔÇÖ self-control at Medan State University, which is quantitatively proven through the results of data analysis.┬á